2009
DOI: 10.1071/bt09165
|View full text |Cite
|
Sign up to set email alerts
|

Water deficit changes the anatomy of the fruit abscission zone in Raphanus raphanistrum (Brassicaceae)

Abstract: Raphanus raphanistrum L. is an important agricultural weed that often matures at a time of year when water availability is decreasing rapidly. We examined the development of the abscission zone under contrasting soil water treatments and exogenous application of Ethrel. Morphometric analyses of cell traits were used to quantify the effects. Although the abscission zone was visible in sections after 2 weeks under all water regimes, it was more distinctive for pods that had developed under water deficit and Ethr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 20 publications
0
10
0
Order By: Relevance
“…Often these signals are associated with the senescence of the distal organ. However, a spectrum of environmental factors, such as a deficit or surplus of water, extremes of temperature, or pest and pathogen attack, can prematurely precipitate leaf, flower, or fruit fall (Taghizadeh et al, 2009;Taylor and Whitelaw, 2001). Understanding how the process of abscission is regulated in model crops would benefit agriculture.…”
Section: Introductionmentioning
confidence: 99%
“…Often these signals are associated with the senescence of the distal organ. However, a spectrum of environmental factors, such as a deficit or surplus of water, extremes of temperature, or pest and pathogen attack, can prematurely precipitate leaf, flower, or fruit fall (Taghizadeh et al, 2009;Taylor and Whitelaw, 2001). Understanding how the process of abscission is regulated in model crops would benefit agriculture.…”
Section: Introductionmentioning
confidence: 99%
“…It has been investigated that lack of water, as one of the most important resources, affects seed attribute including dispersal. For example, Taghizadeh et al, (2009) demonstrated that water deficit increased the size of the cells in the abscission zone of wild radish (Raphanus raphanistrum L.), and abscission scar diameter increased by ~50% with increasing water deficit. This promoted the onset of pod dehiscence.…”
Section: Discussionmentioning
confidence: 99%
“…Eventually, nonetheless, seeds leave their parents through dispersal. An abscission layer usually forms between the maternal tissue and seeds, providing a line of weakness at which the seed can separate (Taghizadeh et al, 2009). Although the act of dispersal begins with the departure of the propagule from the parent plant, many factors contributing to the dispersal trajectory occur very much earlier than this moment (Cousens et al, 2008a;Cousens et al, 2008b;Kelly et al, 2013;Taghizadeh et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…As a result, a variety of chemicals and plant hormones have been used to control fruit abscission (Pozo and Jacqueline, 2009). The fruit abscission zone (AZ) can differ according to internal conditions such as cultivar, fruit maturation, and carbohydrate content (Castillio-Llanque and Rapoport, 2009;Iglesias et al, 2006;Taghizadeh et al, 2009). Agricultural practices such as branch girdling (Murayama et al, 2006), thinning (Zibordi et al, 2009), and harvest period (Lichter et al, 2006) also affect the formation of AZ.…”
Section: Research Reportmentioning
confidence: 99%
“…The shedding of reproductive organs is important for generation succession and dispersal of a species to unoccupied habitats. The process is also a defense mechanism against environmental stresses such as water and light changes (Taghizadeh et al, 2009;Zibordi et al, 2009) and pathogenic attack (Peres et al, 2008).…”
Section: Research Reportmentioning
confidence: 99%